A Collating Study for Health and Management Practices Followed by Stall Fed and Extensive Rearing Goat Farmers of Punjab - Dhaliwal, Aman Deep Singh; Kasrija, Rajesh; Singh, Parminder; Jadoun, Y. S. (International Journal of Bio-resource and Stress Management, 2022)
The present study was conducted in all the six different agro-climatic zones of Punjab state during February 2019 to April 2020 to study the awareness of goat farmers rearing goats on Stall fed (Group I) and Extensive/Grazing (Group II) system regarding health and management practices. A total of 120 goat farmers were randomly selected in such a way that 10 goat farmers belong to Group I and Group II each from all the six different agro-climatic zones, thereby making sample size of 60 goat farmers for Group I and Group II each. Personal interview schedule as tool of data collection was used to gather information. In Punjab, most of the goat farmers were between age group 31-60 years, male, with education level up to high school, had main occupation as goat farming, had joint families and were landless. The mean knowledge percentage at Punjab level was reported to be 33.20%. The health and management knowledge score of Group I and Group II goat farmers in different agro-climatic zones of Punjab differ significantly at p<0.05. The knowledge score of Group I (in medium category) is significantly higher (at p<0.05) than Group II (in Low category). The present study gives light on the facts that there is dire need to enrich knowledge of goat farmers about health and management practices by conducting demonstrations and training programmes at field level. The knowledge level of goat farmers should be assessed before organizing any extension programme, as it varies from zone (area) to zone (area) and between different farming system. Also, the goat farmers should be educated about advantages of stall rearing system, so as to give momentum to goat farming in the state.